Differential target multiplexed spinal cord stimulation using a paddle-type lead placed at the appropriate site for neuropathic pain after spinal cord injury in patients with past spinal surgical histories: study protocol for an exploratory clinical trial - Takafumi Tanei; Satoshi Maesawa; Yusuke Nishimura; Yoshitaka Nagashima; Tomotaka Ishizaki; Masahiko Ando; Yachiyo Kuwatsuka; Atsushi Hashizume; Shimon Kurasawa; Ryuta Saito (Trials, 2023)
Abstract Background Neuropathic pain after spinal cord injury (SCI), both traumatic and non-traumatic, is refractory to various treatments. Spinal cord stimulation (SCS) is one of the neuromodulation therapies for neuropathic pain, although SCS has insufficient efficacy for neuropathic pain after SCI. The reasons are presumed to be inappropriate locations of SCS leads and conventional tonic stimulation itself does not have a sufficient analgesic effect for the pain. In patients with past spinal surgical histories, the cylinder-type leads are likely to be placed on the caudal side of the SCI because of surgical adhesions. Differential target multiplexed (DTM) stimulation is one of the latest new stimulation patterns that is superior to conventional stimulation. Methods A single-center, open-label, randomized, two-way crossover trial is planned to investigate the efficacy of SCS using DTM stimulation placing a paddle lead at the appropriate site for neuropathic pain after SCI in patients with spinal surgical histories. The paddle-type lead delivers energy more efficiently than a cylinder-type lead. This study consists of two steps: SCS trial (first step) and SCS system implantation (second step). The primary outcome is rates of achieving pain improvement with more than 33% reduction 3 months after SCS system implantation. The secondary outcomes are to be evaluated as follows: (1) effectiveness of DTM and tonic stimulations during the SCS trial; (2) changes of assessment items from 1 to 24 months; (3) relationships between the result of the SCS trial and the effects 3 months after SCS system implantation; (4) preoperative factors associated with a long-term effect, defined as continuing for more than 12 months; and (5) whether gait function improves from 1 to 24 months. Discussion A paddle-type lead placed on the rostral side of SCI and using DTM stimulation may provide significant pain relief for patients with intractable neuropathic pain after SCI in patients with past spinal surgical histories. Trial registration Japan Registry of Clinical Trials (jRCT) jRCT 1042220093. Registered on 21 November 2022, and last modified on 6 January 2023. jRCT is approved as a member of the Primary Registry Network of WHO ICTRP.